Synthesis of nanosized hematite supported on hyzeolite for protocatalytic decolourization of methyl orange - Nur Farhana Jaafar, 1989-; Sugeng Triwahyono; Aishah Abdul Jalil, supervisor; Fakulti Sains (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012